Electronic health record data quality variability across a multistate clinical research network - Yahia Mohamed; Xing Song; Tamara M. McMahon; Suman Sahil; Meredith Zozus; Zhan Wang; Greater Plains Collaborative; Lemuel R. Waitman (Journal of Clinical and Translational Science, 2023)
Abstract